2021
DOI: 10.1186/s41747-021-00212-6
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer: comparison of quantitative dual-layer spectral CT and axillary ultrasonography for preoperative diagnosis of metastatic axillary lymph nodes

Abstract: Background Our aim was to compare the diagnostic performance of quantitative dual-layer spectral computed tomography (DLSCT) and axillary ultrasound (US) for diagnosing lymph node metastases in breast cancer patients. Methods DLSCT and axillary US were prospectively performed in 70 needle biopsy-verified breast cancer patients. Histopathology and imaging data were available for evaluation in 36 axillae from 34 patients. In each patient, ipsilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Additionally, Eff-Z, another quantitative index for different materials which represents the composite atom for a compound or mixture of various materials and is important to predict how x-rays interact with a substance [7], was analyzed in the current study. Previous studies have indicated that Eff-Z could depict lesion characterization and could be used to differentiate tumors[16, [23][24][25]. In our study, the same conclusions were reached.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, Eff-Z, another quantitative index for different materials which represents the composite atom for a compound or mixture of various materials and is important to predict how x-rays interact with a substance [7], was analyzed in the current study. Previous studies have indicated that Eff-Z could depict lesion characterization and could be used to differentiate tumors[16, [23][24][25]. In our study, the same conclusions were reached.…”
Section: Discussionsupporting
confidence: 89%
“…One thousand two hundred and thirty‐seven duplicate records were removed. After screening 2631 titles and abstracts and 94 full texts, 61 articles 15,17–26,41–90 proved eligible. The detail of the study selection process is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a study, 12 the online arterial phase λ Hu and NIC, the venous phase λ Hu , NIC, and nZeff of metastatic sentinel lymph node were higher than those of nonmetastatic sentinel lymph nodes. Other studies 12,19 have also shown that λ Hu at venous phase obtained through DECT had a high diagnostic performance for the preoperative diagnosis of sentinel lymph node metastases in participants with breast cancer. Zhang et al 15 also found axillary lymph node metastasis and primary tumor λ Hu were basically the same.…”
Section: Preoperative Diagnosis Of Metastatic Sentinel Lymph Nodesmentioning
confidence: 88%